Basic motor abilities: Predictive value on the situational test results in 12-14 years old soccer players - Becirovic, E.; Ismaili, H.; Kapidzic, A. (Serbian Journal of Sports Sciences, 2010)
In a number of anthropological sciences, research on mutual relations between the dimensions of real subsystems and between different subsystems within a system has a significant place. To successfully manage a system, such as man, one must know the structure of certain subsystems within the system and their mutual relations. The main aim of this study was to determine the impact of the predictive system of variables (basic motor ability) against the criterion set of variables (situational motor ability). The test sample in this survey were the students of school clubs FC "Sloboda", FC "Tuzla" and FC "KLUB-7" based in Tuzla of 12-14 years of age. The students of all three soccer schools were members of the pioneer competition selection in the above mentioned soccer clubs. The average age of the respondents who comprised the sample ranged within 13±1 years. Factor analysis was used with the intention to perform factorization of variables of the situational motor ability in order to find a general situational motor ability. Regression analysis was used to determine the impact of the predictive system of variables (basic motor ability) against the criterion. The analysis of the obtained results showed that the applied basic motor variables are dominantly responsible for achieving better results in players` situational motor abilities. Four out of fifteen applied variables showed statistically significant partial effect on the criteria, i.e.: MBFTAN - leg tapping, MFLBOS - side legs wide spread, MES20V - running 20 m (sprint), MBAU2O - standing upright on both legs with eyes open. In this study there were detected the abilities of most influence on improving results in tests of situational motor abilities. This information can contribute to more efficient means of selecting exercises that would be applied in working with young players. At the end, we have to say that excellent success is only possible if the athletes` preparation process and sport itself are based on scientifically founded tendencies, and this is probably the only and the right way in guiding our league competition towards contemporary attainments of the soccer game.